Combination of two bacterial strains Bradyrhizobium sp and Bacillus sp as Biofertilizer and Biocontrol in the Cultivation of Tarwi (Lupinus mutabilis Sweet) in the Peruvian Highlands - Camarena, elix (2023)
It is very important to know adequately the association of beneficial microorganisms of soil with crops, in order to learn on its biofertilizer and biocontrol effects, which will allow to improve the growth and yield of the crops. The evaluation of the co-inoculation of bacteria that promote plant growth by different mechanisms in plants challenged by pathogens would contribute to increase the knowledge of the interactions of plants with different microorganisms. The aim of this research was to evaluate the biofertilizer and biocontroller effects through the bioinoculations of Bradyrhizobium and Bacillus spp. strains association. Both effects were measured during plant growing through the variable response against to Anthracnose disease on yield and seed nutrient content, using Altagracia variety. The experiment was carried out in Paltash locality at 3100 m.a.s.l. in the District of Marcará, Carhuaz, Ancash Region. Three treatments were tested: i) Bradyrhizobium + Bacillus bioinoculants, ii) a chemical treatment, and iii) a control (without bioinoculants or chemicals). The field experiment was carried out under randomized complete block design (RCBD) with four blocks. The following parameters were evaluated: 1) The fresh and dry weight of the aerial part, root and nodules at 60 days; 2) Anthracnose severity during flowering, pod filling and harvesting; and 3) Seed nutrient content. Statistical analysis was performed using Duncan’s test (95 % CI). Results obtained indicate that the bioinoculated plants presented the best nodule characteristics; likewise, bioinoculation reduced the degree of Anthracnose severity in the different phenological stages. It is concluded that bioinoculations improved tarwi growth and anthracnose control.